Prevalence and Distribution of Human Papillomavirus Genotypes Among Women in Kinshasa, The Democratic Republic of the Congo - Alex B. Mutombo; Ina Benoy; Rahma Tozin; Johannes Bogers; Jean-Pierre Van geertruyden; Yves Jacquemyn (Journal of Global Oncology, 2019)
PURPOSE: Cervical cancer is the leading cause of mortality by cancer in sub-Saharan Africa. The human papillomavirus (HPV) infection is recognized as a necessary and sufficient cause for cervical cancer. Population-specific estimates of HPV prevalence in the Democratic Republic of the Congo (DRC) are unknown. This study aims to estimate the prevalence of HPV and identify predominant genotypes circulating in Kinshasa, DRC. METHODS: Between July 2015 and July 2017, women were invited to attend a screening program at Mont-Amba Health Centre in Kinshasa. Cervical specimens were collected using the Preservcyt medium. HPV DNA testing was performed for all specimens using real-time polymerase chain reaction. RESULTS: During the 2-year period, a total of 1,870 women age 25 to 82 years were screened. The mean age was 46 years (± 11.4 years). The overall HPV prevalence was 28.2% (95% CI, 26.1% to 30.3%). High-risk HPV prevalence was 24.8% (95% CI, 22.8% to 26.8%). Women younger than 30 years had the highest overall HPV prevalence (42.2%; 95% CI, 34.7% to 49.9%). A second peak of prevalence was observed in women age 60 years and older. HPV68 (5.5%; 95% CI, 4.5% to 6.6%) was the most prevalent HPV type. CONCLUSION: The distribution of HPV genotypes among women in our population was different compared with other world regions. A key finding was that HPV68 was the most prevalent high-risk HPV genotype. These findings highlight the need for the determination in our population of the etiologic fraction of different HPV types in invasive cervical cancers.